The Best American Short Stories, 2001 : selected from U.S. and Canadian magazines - Kingsolver, Barbara; Kenison, Katrina (Boston : Houghton Mifflin, 2001)
The acclaimed annual short fiction series - this year featuring guest editor Barbara Kingsolver - presents a collection of 2001 stories selected from magazines in the United States and Canada.
Foreword -- Introduction / Barbara Kingsolver -- Servants of the map / Andrea Barrett -- The fireman / Rick Bass -- Think of England / Peter Ho Davies -- Labors of the heart / Claire Davis -- The mourning door / Elizabeth Graver -- After Cowboy Chicken came to town / Ha Jin -- Brothers and sisters around the world / Andrea Lee -- Boys / Rick Moody -- Rug weaver / Barbara Klein Moss -- Post and beam / Alice Munro -- The raft / Peter Orner -- Betty Hutton / Roy Parvin -- Illumination / Nancy Reisman -- The secrets of bats / Jess Row -- Nobody listens when I talk / Annette Sanford -- My mother's garden / Katherine Shonk -- What I saw from where I stood / Marisa Silver -- The apple tree / Trevanian -- Personal archeology / John Updike -- My baby... / Dorothy West -- Contributors' notes -- 100 other distinguished stories of 2000 -- Editorial addresses of American and Canadian magazines publishing short stories.
Keywords: Short stories, American; Short stories, Canadian; American fiction -- 21st century; Canadian fiction -- 21st century